Twenty Years of the Arctic Council: International Law Aspects - D. Yu. Lyapchev (Московский журнал международного права, 2016)
The article covers the development and international law aspects of the Arctic Council formed in 1996 by the eight Arctic states in order to face the challenges of the global warming and the climate changes in the region. The two adopted legally binding documents are discussed and appraised on the basis of the existing international law and an overall assessment of the undertaken activities is given, as well as a forthcoming development analysis. Most notable other activities include: landmark studies on the pollutants, conservation of biodiversity and climate change; nine political declarations; the Arctic Economic Council establishment and the conclusion of the Framework for Action on Enhanced Black Carbon and Methane Emissions Reductions.